Assessing Market Risk of Indian Index Funds. (June 2015) - Biswas, Suparna; Dutta, Santanu
An index fund is a mutual fund that aims to imitate a benchmark index. In India, there has been significant growth in the number of such funds since 2002. These funds are exposed mainly to market risk. The assessment and comparison of the market risk and the risk-adjusted returns of these funds are topics of interest to both researchers and investors. Value-at-risk and expected shortfall are well-known measures of the market risk. The Sharpe ratio and the Treynor ratio measure risk-adjusted return earned in excess of average market return. For each fund, we estimate these measures. Most of the index funds exhibit similar market risk as the NIFTY or the SENSEX index, which they mimic. Moreover, the market risk of these funds seems to be unaffected by multiple-fund management by the respective fund managers. However, there exist significant differences among the risk-adjusted daily returns, earned in excess of the average daily index return, of the various Indian index funds. Ideally, an index fund is expected to exhibit similar risk and risk-adjusted return as the benchmark index. We identify some such Indian index funds.